Commercial babassu mesocarp: microbiological evaluation and analysis of label information - Laisa Lis Fontinele Sá; Tamyres Andrade Macedo; Sean Teles Pereira; Nouga Cardoso Batista; Lívio Cesar Cunha Nunes; Waleska Ferreira Albuguergue (São Paulo State University (UNESP), 2015)
The babassu mesocarp is easily found in supermarkets and other commercial establishments in Brazil. Despite its widespread use in both pharmaceutical and food industries, the literature has neither scientific studies about microbial contamination for these products nor about legal information expressed on label. The aim of this study was to evaluate the level of microbiological contamination in babassu mesocarp sold in commercial establishments in Teresina-PI/Brazil besides the conformity of label information according to the rules of Brazilian Sanitary Surveillance Agency (ANVISA). Ten samples of babassu mesocarp powder sold in the region were selected for study. Determination of heterotrophic microorganisms was carried out using the seeding technique of Plate Count Agar (CFU g-1). It was used Sabouraud Dextrose Agar medium for cultivation of fungi. For the analysis of label information, the resolutions (RDC), 259 of September 20, 2002, and 360 of December 23, 2003, beyond the law 10,674 of May 16, 2003 were used. The results of levels of contamination for heterotrophic bacteria and fungi showed high contamination for all samples. Most of the label samples were according to the rules. Therefore, the results suggest a more comprehensive monitoring of these microorganisms besides the development of more effective methods for decontamination of these products sold in Brazil. Keywords: Babassu. Label. Contamination. Food. Pharmacy.   RESUMO   O mesocarpo de babaçu é encontrado facilmente em supermercados e em outros estabelecimentos comercias e apesar de sua ampla utilização, tanto na indústria farmacêutica e de alimentos, na literatura não há trabalhos científicos que avaliem sua contaminação microbiológica ou informações legais necessárias para rótulos. O objetivo do estudo foi avaliar o nível de contaminação microbiológica do mesocarpo de babaçu, vendidos no comércio de Teresina-PI, bem como verificar a conformidade das informações dos rótulos com as normas da Agencia de Vigilância Sanitária (ANVISA). Foram selecionadas dez amostras do pó comercializadas no mercado regional. Para a determinação de microrganismos heterotróficos foi realizada a técnica de semeadura utilizando o meio Plate Count Agar, para fungos, utilizou-se o meio Sabouraud Dextrose Ágar e para a avaliação dos rótulos tomaram-se como base as resoluções, RDC 259, de 20/09/2002, RDC 360, de 23/12/2003, e a Lei nº10.674, de 16/05/2003. Os resultados dos índices de contaminação para bactérias heterotróficas e fungos mostraram-se bastante elevados. Quanto à rotulagem, a maioria das amostras estava de acordo com as regras. Com os resultados obtidos sugere-se um monitoramento mais abrangente desses microrganismos além do desenvolvimento de métodos de descontaminação mais efetivos para esses produtos comercializados no Brasil. Palavras-chave: Babaçu. Rótulos. Contaminação. Alimentos. Farmácia.